NURSING IMPLEMENTATION OF DISTRACTION TECHNIQUES: MUROTAL QUR'AN IN PATIENT POST URETERLITOTOMY (Proceedings OPTIMAL, 2024)
Background: Perioperative nursing is a nursing process for developing individual care plans and coordinating and providing care to patients undergoing surgery or procedures. The aim of this research is to determine whether the implementation of the Murotal Qur'an technique is effective in reducing the pain scale in post-operative ureterlithotomy patients. Method: descriptive research with a case study approach, with a time of 12 minutes when pain appears. Results: Implementation of the nursing action of the Qur'an murotal technique in Surah ArRahman for 3 days showed that pain was reduced, this proves that the act of providing the Qur'an murotal technique can influence the process of reducing pain intensity. On the first day the author got pain scale data of 8 from (0-10) to 6, on the 2nd day the patient's pain scale was from 6 to 4, on the 3rd day the author got data on the patient's pain scale from 4 to 2. Qur'an murotal technique can influence the process of reducing pain intensity in post-operative ureterlithotomy patients. It is hoped that this therapy can be applied by nurses in overcoming the nursing problem of acute post-operative ureterlithotomy pain and that patients can apply it independently in dealing with pain.